Influence of a near-electrode layer thickness on the diffusion impedance - Pototskaya, V.V.; Gichan, О.І.; Skryptun, I.N.; Omel'chuk, A.A. (Reports of the National Academy of Sciences of Ukraine, 2018)
It is shown that the impedance of a near-electrode layer increases with the thickness of the Nernst diffusion layer. A qualitative estimation of the phase angle of the diffusion impedance depending on the frequency at different diffusion layer thicknesses is obtained. It is shown that the diffusion is a reason for a delay in the phase of changes in the surface concentration of species with respect to the current.